Human Lactation in the Anthropocene: a Post-pandemic Emergency - Massó Guijarro, Ester (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2021)
Human lactation was declared a human right by the UN Human Rights Council in 2016, due to its universal condition, and it is defined as one of the social investments with highest cost-benefit ratio, according to the 2030 Sustainable Development Agenda. Despite all this, its holistic approach as a hypercomplex phenomenon within the framework of human development remains dramatically absent, urgency that has been increased by the syndemic crisis in the cosmological context of the Anthropocene.